2016
DOI: 10.1088/1367-2630/18/9/092002
|View full text |Cite
|
Sign up to set email alerts
|

Confinement of phonon propagation in laser deposited tungsten/polycarbonate multilayers

Abstract: Nanoscale multilayer thin films of W and PC (Polycarbonate) show, due to the great difference of the components' characteristics, fascinating properties for a variety of possible applications and provide an interesting research field, but are hard to fabricate with low layer thicknesses. Because of the great acoustic mismatch between the two materials, such nanoscale structures are promising candidates for new phononic materials, where phonon propagation is strongly reduced. In this article we show for the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
12
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 44 publications
(49 reference statements)
1
12
0
2
Order By: Relevance
“…This interesting direction-dependent elastic wave propagation blocking could be experimentally proved by observing the reflectivity signal from the top of the SL. Indirectly, Döring et al [8] have revealed this effect though the localization of the observed resonance mainly into the thick (20.2 nm) W layer on the top of the SL.…”
mentioning
confidence: 96%
See 4 more Smart Citations
“…This interesting direction-dependent elastic wave propagation blocking could be experimentally proved by observing the reflectivity signal from the top of the SL. Indirectly, Döring et al [8] have revealed this effect though the localization of the observed resonance mainly into the thick (20.2 nm) W layer on the top of the SL.…”
mentioning
confidence: 96%
“…Writing in New Journal of Physics, Döring et al [8] report the growth of hard tungsten, (W)/soft (polycarbonate, PC) SL by pulsed laser deposition (PLD) with low interfacial roughness and sharp periodicity of the order of 20 nanometers. The utilization of the fabrication technique for polymer deposition is not trivial because of material degradation and ill-defined packing that can significantly impact the soft layer properties.…”
mentioning
confidence: 99%
See 3 more Smart Citations